Rhythms in Plants 2015
DOI: 10.1007/978-3-319-20517-5_6
|View full text |Cite
|
Sign up to set email alerts
|

The Pollen Tube Oscillator: Integrating Biophysics and Biochemistry into Cellular Growth and Morphogenesis

Abstract: Individual cells generate ultradian rhythms in different systems and levels of organisation. A cell biology approach is necessary to better understand the intrinsic nature of these biological oscillators and their evolutionary significance. In this respect, pollen tubes provide a useful working model because, unlike other cells, their growth can be conveniently followed in vitro and it is known to involve structural, biochemical as well as biophysical oscillations. As commonly seen in complex systems, these os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 159 publications
0
10
0
Order By: Relevance
“…Pollen tubes (PTs) are highly polarized cells that employ temporally and spatially coordinated cellular processes to achieve apical growth rates that are among the fastest known in nature ( Boavida et al , 2005 ). Oscillatory behaviour in PTs (reviewed in Feijó et al , 2001 ; Portes et al , 2015 ; Damineli et al , 2017 b ) may occur within a characteristic range of frequencies found in apical growth and related cellular processes, such as tip-localized ion fluxes ( Feijó et al , 2001 ), intracellular ion concentration (Ca 2+ , H + , Cl − ; Holdaway-Clarke et al , 1997 ), cytoskeleton dynamics (F-actin; Fu et al , 2001 ), membrane trafficking ( Parton et al , 2001 ), ROP signalling ( Hwang et al , 2005 ), NAD(P)H levels ( Rounds et al , 2010 ), and cell wall synthesis ( Pierson et al ,1995 ; Rounds et al , 2014 ). However the identity of the ‘pacemaker(s)’ underlying the oscillations and their physiological role in growth, cell polarity, and guidance is yet to be determined ( Damineli et al , 2017 b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollen tubes (PTs) are highly polarized cells that employ temporally and spatially coordinated cellular processes to achieve apical growth rates that are among the fastest known in nature ( Boavida et al , 2005 ). Oscillatory behaviour in PTs (reviewed in Feijó et al , 2001 ; Portes et al , 2015 ; Damineli et al , 2017 b ) may occur within a characteristic range of frequencies found in apical growth and related cellular processes, such as tip-localized ion fluxes ( Feijó et al , 2001 ), intracellular ion concentration (Ca 2+ , H + , Cl − ; Holdaway-Clarke et al , 1997 ), cytoskeleton dynamics (F-actin; Fu et al , 2001 ), membrane trafficking ( Parton et al , 2001 ), ROP signalling ( Hwang et al , 2005 ), NAD(P)H levels ( Rounds et al , 2010 ), and cell wall synthesis ( Pierson et al ,1995 ; Rounds et al , 2014 ). However the identity of the ‘pacemaker(s)’ underlying the oscillations and their physiological role in growth, cell polarity, and guidance is yet to be determined ( Damineli et al , 2017 b ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the study of apical growth, rough estimates of the PT tip location are extracted from kymographs (a plot of single dimension of space through time) or with dedicated software applied to videos ( Certal et al , 2008 ; Gutermuth et al , 2013 ; Portes et al 2015 ). While there has been a wide array of methods used to detect the PT tip and track growth or changes in tip morphology, some of which achieve resolution below the pixel limit (subpixel), all methods developed so far involve either complex algorithms or model fitting ( Holdaway-Clarke et al , 1997 ; Messerli et al , 1999 ; Rojas et al , 2011 ; Haduch-Sendecka et al , 2014 ; Tambo et al , 2015 a , b ; Tambo and Bhanu, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the flux of Cl 2 was found to be in phase with growth (Zonia et al, 2002). Nevertheless, different estimates of advances and delays have been collected in a variety of biological systems like lily (Lilium longiflorum), tobacco (Nicotiana tabacum), petunia (Petunia hybrida), less in Arabidopsis (Arabidopsis thaliana), using imaging techniques (differential interference contrast, wide-field or confocal fluorescence), and electrophysiology methods in such ways that comparisons of the published delays and proposed sequences of events are subject to potential distortions (Portes et al, 2015;Daminelli et al, 2017). Last but not least, correlation does not imply causation, and not much can be deduced from those studies, particularly because we do not know the kinetic properties of key reactions within the networks, such as molecular diffusion, protein phosphorylation, exocytosis, etc.…”
Section: Pollen Tubes As a Tailored Model For Studying Ion Dynamics Amentioning
confidence: 99%
“…'Another brick in the cell wall' that considers-at the microscopic level-cytosolic approaches to oscillations has been reviewed by Portes et al [33]. The authors, seeking a missing pendulum, reviewed the pollen tube oscillator as integrating biophysical and biochemical aspects of cellular growth.…”
Section: Discussionmentioning
confidence: 99%